Doctoral Journey of a Management Scholar: A Viewpoint. (September 2015) - Mishra, Pavitra
A doctoral journey involves exploration of unknown areas and new prospects. It provides a chance of rebirth and change, but also has a risk of uncertainty. This article is a reflection of my doctoral journey. It explains various stages of a doctoral journey. It also highlights some useful strategies and attitudes required for successful completion of this journey. The article aims to help young doctoral scholars in understanding important aspects of a doctoral research.